2022
DOI: 10.1177/17511437221103689
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of physical activity interventions on delirium outcomes in intensive care unit patients: A systematic review and meta-analysis

Abstract: Background To investigate the impact of physical activity interventions, including early mobilisation, on delirium outcomes in critically ill patients. Methods Electronic database literature searches were conducted, and studies were selected based on pre-specified eligibility criteria. Cochrane Risk of Bias-2 and Risk Of Bias In Non-randomised Studies-of Interventions quality assessment tools were utilised. Grading of Recommendations, Assessment, Development and Evaluations was used to assess levels of evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Unfortunately, they found only low-quality evidence in favor of greater-intensity PA. They concluded that there was insufficient evidence to recommend PA as a stand-alone intervention to reduce delirium in the ICUs [5].…”
Section: Outcomes After Icu Staymentioning
confidence: 99%
“…Unfortunately, they found only low-quality evidence in favor of greater-intensity PA. They concluded that there was insufficient evidence to recommend PA as a stand-alone intervention to reduce delirium in the ICUs [5].…”
Section: Outcomes After Icu Staymentioning
confidence: 99%